The Impact of Land Use Change on Hydrological Response in Watersheds Batang Merao - Ollga Febiola (AKADEMI TEKNIK ADI KARYA, 2025)
Intensive sand mining in the Siulak Deras area, Kerinci Regency, has had a serious impact on the ecosystem of the Cumbadak River and Tuak River. This activity triggers damage to river morphology, decreased water quality, and disrupts the balance of aquatic ecosystems. This research aims to formulate appropriate environmental management strategies to reduce and control the negative impacts of sand mining activities in the area. The approach used was a SWOT analysis and TOWS strategy matrix, combined with the results of field observations and in-depth interviews with relevant stakeholders. The results of the study show that weak supervision, lack of community involvement, and inconsistent implementation of environmental documents are the main challenges in managing the impacts of sand mining. The recommended strategies include strengthening community-based supervision, implementing environmentally friendly technology, revitalizing watersheds, and increasing transparency in the implementation of EIAs. With the implementation of this strategy, it is hoped that there will be synergies between economic activities and sustainable environmental conservation in Kerinci Regency.